POLARIS: VIRUS-SAFE COMPUTING for Windows XP. (Communications of the ACM, 2006)
This article reports on ways to limit the amount of damage that can be caused by computer software viruses. The author believes that putting an end to the excess authority that every computer program gets from the operating system is the key to limiting the negative impact of viruses. The author also discusses Polaris, a package for Windows XP that is being developed by a group called the Virus Safe Computing Initiative at Hewlett-Packard Laboratories. The package allows users to configure most applications so that they launch with just the specific rights that the user requires. INSETS: VIRUSES AND WORMS;PRIVILEGE, PERMISSION, AND AUTHORITY.